Has Job Satisfaction been Affected by Islamic Leadership, Remuneration, or Organizational Citizenship Behavior? - Qurratul Aini; Mustafa Musa Jaber (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
Numerous hospital managers are unsatisfied with their positions, limiting their capacity to enhance the quality of hospital services. Even though personnel demand better remuneration to enhance their performance, this may harm hospital impressions. By fostering a culture of Organizational Citizenship Behavior (OCB) and enhancing employee job satisfaction, Islamic leadership styles may assist in achieving a balance between employee compensation expectations and organizational resources. This study aims to determine the impact of Islamic leadership and compensation on organizational citizenship behavior and job satisfaction at a private hospital. Method: The research employed a quantitative cross-sectional methodology, collecting primary data with Google Forms and analyzing it with Smart PLS. Respondents who are permanent staff at private hospitals in Klaten were handed questionnaires. This study intended a total sample size of 98 employees, and only 90 responses meeting the inclusion criteria were gathered. This survey was conducted in July 2021, with questionnaires customized to the conditions of the research site based on previous research. Result: As a result of the inclusion criteria and data-gathering procedures, ninety replies were gathered. OCB is influenced by remuneration and Islamic leadership because Islamic leadership can operate as a counterweight to workers' desire for high remuneration due to the emergence of OCB behavior in the hospital setting. Generally, well-compensated employees are more content with their jobs. Consequently, OCB behavior has a minor impact on job satisfaction. Conclusion: The relationship between Islamic leadership and remuneration and organizational citizenship behavior and job satisfaction is significant.